Preparation method of high-strength corrosion-resistant copper alloy
By using Ni-Cr intermediate alloy and deformation heat treatment process in copper alloy, the problem of low solid solubility in copper is solved, and the high strength and corrosion resistance of copper alloys are improved, the processing technology is simplified and the reduction is reduced. The cost.
Patent Information
- Application Number
- CN202411386924.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing copper alloy preparation methods, the solid solubility of Cr elements in copper is low in room temperature, which makes it difficult to evenly distribute Cr elements, and cannot effectively improve the strength and corrosion resistance of copper alloys, and the complex processing process increases costs.
By introducing Cr elements using Ni-Cr intermediate alloy and combining with deformation heat treatment technology, uniform distribution of Cr and improving high-strength corrosion resistance, Ni and Mn elements are used for solid solution strengthening and precipitation strengthening to form nano-scale NiMn precipitation phase , improve the mechanical properties and corrosion resistance of the alloy.
It realizes the coordinated improvement of high strength and corrosion resistance of copper alloys, reduces corrosion rate, simplifies processing technology, reduces production costs, and is suitable for large-scale production.
Smart Images

Figure CN119287191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-based alloys, and in particular to a method for preparing a high-strength, corrosion-resistant copper alloy. Background Art
[0002] Copper alloys have good mechanical properties and corrosion resistance and are widely used in marine engineering, aerospace, electrical and electronic fields. With the rapid development of science and technology and industry and the increasingly harsh service environment, higher requirements are placed on the performance of high-strength and corrosion-resistant copper alloys.
[0003] The Chinese invention patent with authorization announcement number CN115896537B, which was authorized on April 2, 2024, discloses a high-strength, corrosion-resistant Cu-Ni-Sn alloy and a preparation method thereof. The Cu-Ni-Sn alloy includes the following components in mass percentage: Ni: 14-17%, Sn: 7.0-9.0%, Al: 0.6-1.5%, Zn: 0.2-0.8%, Cr: 0.05-0.5%, Nb: 0.05-0.5%, Zr: 0.05-0.15%, and the balance is Cu. A multi-stage homogenization heat treatment process is used to eliminate Sn segregation inside the alloy, and combined with the addition of other micro-alloying elements, the strength and corrosion resistance of the Cu-Ni-Sn alloy are improved.
[0004] The Chinese invention patent with authorization announcement number CN111004936B, which was authorized on February 2, 2022, discloses a method for preparing a high-strength and high-corrosion-resistant Cu-Ni-Mn alloy. The Cu-Ni-Mn alloy ingot is subjected to hot extrusion treatment, combined with room temperature cold rolling treatment with large deformation and electric pulse treatment, so that the grains are refined, and the θ-MnNi precipitate is partially dissolved back into the α-Cu matrix, and defects such as dislocations are partially restored, thereby reducing the corrosion tendency of the alloy, thereby ensuring that the alloy has high strength while improving the corrosion resistance of the alloy.
[0005] However, the preparation of the above two copper alloys requires a complex post-processing process, which greatly increases the processing cost of the copper alloy. Therefore, there is an urgent need for a method that can simply adjust the composition of the copper alloy to improve the strength and corrosion resistance of the copper alloy. The Cr element has a good effect of strengthening mechanical properties and improving corrosion resistance, but the room temperature solid solubility of Cr in copper is extremely low, less than 1%. Therefore, in the conventional preparation method, it is difficult for the Cr element to be evenly dispersed in the copper matrix, and it is difficult to play a strengthening and corrosion resistance effect. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a high-strength corrosion-resistant copper alloy to solve the problem that the existing copper alloy has poor mechanical properties and corrosion resistance.
[0007] In order to solve the above technical problems, the technical solution of the method for preparing the high-strength corrosion-resistant copper alloy of the present invention is:
[0008] A preparation method of a high-strength corrosion-resistant copper alloy comprises the following steps: smelting copper, manganese and Ni-Cr master alloy according to the designed composition of the copper alloy and then casting to obtain a copper alloy ingot, and performing deformation heat treatment on the copper alloy ingot, wherein the mass fraction of Cr in the copper alloy is 5-7%.
[0009] The preparation method of the high-strength corrosion-resistant copper alloy provided by the present invention can avoid the problem that the room temperature solid solubility of Cr in Cu is low, less than 1%, and it is difficult to directly add a high content of Cr by adding a Ni-Cr master alloy to introduce Cr, and the mutual solid solubility between Ni and Cu, Ni and Cr is high. Therefore, by smelting copper, manganese and Ni-Cr master alloy, a copper alloy ingot with a high Cr content and uniform distribution of alloy elements can be obtained, and the high strength and corrosion resistance of the copper alloy are synergistically improved by adjusting the alloy composition and the deformation heat treatment process. The preparation method of the present invention has a simple process and low cost, and is suitable for large-scale production of high-strength corrosion-resistant copper alloys.
[0010] The high-strength corrosion-resistant copper alloy obtained by the preparation method of the present invention, the Cu-Ni-Cr alloy has solid solution strengthening, spinodal decomposition and precipitation strengthening. An appropriate amount of Mn element is introduced on the basis of the Cu-Ni-Cr alloy, and the synergistic improvement of mechanical properties and corrosion properties can be achieved through multiple strengthening mechanisms such as solid solution strengthening, precipitation strengthening, spinodal decomposition and ordered phase: Ni can be infinitely dissolved in Cu to form a continuous solid solution, and has good corrosion resistance; Cr is added to the Cu-Ni binary alloy as a strengthening element and a passivating element, and a spinodal decomposition structure is further introduced to obtain good strength, corrosion resistance and oxidation resistance; Mn is isomorphic to Cu, has a strong solid solution strengthening effect in Cu, is easy to form a second phase with alloy elements, and can effectively regulate the precipitation of the second phase to make the aging precipitation strengthening effect stronger; the solid solution strengthening of Ni and Mn elements and the nano-scale NiMn precipitation phase in the alloy can achieve high strength of the alloy. In addition, through the introduction of high Cr content, the high content of Cr2O3, Cu2O and MnO2 in the alloy corrosion product film formed in the NaCl corrosion environment hinders the transmission of the corrosive medium to the matrix to a certain extent, significantly reduces the corrosion rate of the copper alloy, and improves the corrosion resistance of the copper alloy. It is expected to become a new type of engineering material to be used in seawater environment.
[0011] In order to further improve the corrosion resistance of the copper alloy with high Cr content, preferably, the copper alloy consists of the following components in mass fraction: Ni 15-21%, Cr 5-7%, Mn 5-7% and the balance copper.
[0012] In order to further improve melting uniformity, preferably, the melting temperature is 1200-1300°C.
[0013] In order to further improve the solidification performance of the copper alloy, preferably, the pouring temperature during the casting is 1100-1200°C.
[0014] In order to further improve the mechanical properties and corrosion resistance of the copper alloy, preferably, the thermomechanical treatment includes homogenization treatment, forging, solution treatment, cold rolling and aging treatment performed in sequence.
[0015] The purpose of homogenization treatment is to make the chemical composition of the material more evenly distributed, thereby improving the performance of the material; the purpose of forging is to eliminate defects such as shrinkage cavities and pores in the cast material, optimize the internal microstructure of the material, and improve the mechanical properties; the role of solution treatment is to dissolve the alloying elements into the lattice of the base metal to form a solid solution and obtain a uniform microstructure; the purpose of cold rolling deformation is to introduce a work hardening effect, refine the grains, and promote the movement of dislocations inside the material. At the same time, the storage of high-density dislocations is also conducive to the next step of aging precipitation; aging is after deformation, the material is cooled to a lower temperature and maintained at this temperature for a period of time. At this stage, due to the decrease in temperature, the previously dissolved alloying elements will gradually precipitate from the solid solution to form strengthening phases. These strengthening phases can significantly improve the hardness and strength of the material. Aging treatment is usually carried out at a much lower temperature than the solution treatment temperature to promote the formation of precipitation phases without causing grain growth.
[0016] In order to further eliminate segregation and ensure the uniformity of alloy elements, preferably, the temperature of the homogenization treatment is 1000-1200° C., and the time of the homogenization treatment is 12-14 hours.
[0017] In order to further eliminate defects of the cast metal, preferably, the deformation amount of the forging is 60% to 70%.
[0018] In order to further enhance the solid solution strengthening effect and improve the strength of the copper alloy, preferably, the temperature of the solid solution treatment is 800-900° C. and the time of the solid solution treatment is 3-5 hours.
[0019] In order to distribute the fine dispersed precipitate phase in the matrix and thus improve the strength of the copper alloy, preferably, the deformation amount of the cold rolling is 90-95%, and the cold rolling adopts multiple rolling passes, and the deformation amount of each pass is 5-6%. During the cold rolling process, in order to avoid strong temperature changes, the thinning amount of each pass, that is, the deformation amount, is maintained at 5-6%.
[0020] In order to further precipitate the nano-scale NiMn precipitate phase and improve the strength of the copper alloy, preferably, the temperature of the aging treatment is 400-700° C., and the time of the aging treatment is 300-500 min. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XPS spectrum of the corrosion product film of Cu-19Ni-6Cr-7Mn alloy immersed in 3.5wt% NaCl solution for 30 days. DETAILED DESCRIPTION
[0022] The technical concept of the high-strength corrosion-resistant copper alloy of the present invention is as follows:
[0023] A preparation method of a high-strength corrosion-resistant copper alloy comprises the following steps: smelting copper, manganese and Ni-Cr master alloy according to the designed composition of the copper alloy and then casting to obtain a copper alloy ingot, and performing deformation heat treatment on the copper alloy ingot, wherein the mass fraction of Cr in the copper alloy is 5-7%.
[0024] In the prior art, when introducing Cr element into copper alloy to improve the mechanical properties and corrosion resistance of the alloy, due to the extremely low room temperature solid solubility of Cr in copper, the direct introduction method makes it difficult for the Cr element to be evenly dispersed in the copper matrix, thereby failing to play a role in strengthening and corrosion resistance. The present invention introduces Cr by adding Ni-Cr master alloy, which can avoid the problem that the room temperature solid solubility of Cr in Cu is low, less than 1%, resulting in difficulty in directly adding a high content of Cr, so that the Cr element can be evenly dispersed in the copper matrix, thereby improving the mechanical properties and corrosion resistance of the copper alloy.
[0025] In a specific implementation, the copper alloy consists of the following components in mass fractions: Ni 19-21%, Cr 6-7%, Mn 6-7% and the balance copper.
[0026] In a specific embodiment, the metal raw materials used in the smelting are pure copper (99.99%), electrolytic manganese (99.99%) and Ni-Cr master alloy.
[0027] In a specific implementation, during the smelting, copper is smelted first, and then manganese is added for smelting after the copper is melted, and then the Ni-Cr master alloy is added after the manganese is melted.
[0028] In a specific embodiment, during the smelting, charcoal is added to prevent oxidation when smelting copper, and cryolite is added to prevent oxidation of manganese when smelting manganese.
[0029] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.
[0030] 1. Specific embodiments of the method for preparing the high-strength corrosion-resistant copper alloy of the present invention
[0031] Example 1
[0032] The preparation method of the high-strength corrosion-resistant copper alloy of this embodiment is as follows:
[0033] 1) Melting and casting: A medium frequency induction furnace is used to prepare a Cu-Ni-Cr-Mn alloy according to the following copper alloy composition: Ni 19%, Cr 6%, Mn 7% and the balance copper, the raw materials are pure copper (99.99%), electrolytic manganese (99.99%) and Ni / Cr=3 (mass ratio) Ni-Cr intermediate alloy is smelted: the graphite crucible is preheated by being placed in an electromagnetic induction coil, and then pure copper is added to the crucible for further heating. During heating, it is fully stirred with a graphite rod, and a small amount of charcoal is added to prevent oxidation; after the pure copper is melted, pure manganese and a small amount of cryolite (to prevent manganese oxidation) are placed in the crucible for heating, after the electrolytic manganese is melted, the Ni-Cr intermediate alloy is added to the crucible for further heating, during the whole process, a small amount of carbon black is gradually added to create an air-isolated environment to prevent oxidation, finally, the molten mixture is poured into a mold to complete the casting process, the casting mold adopts a high-purity graphite crucible with a size of 100×200mm, the smelting temperature is controlled at 1200°C, the pouring temperature is controlled at 1100°C, and after the casting is completed, a Cu-19Ni-6Cr-7Mn copper alloy ingot is obtained.
[0034] 2) Deformation heat treatment: To eliminate segregation, the copper alloy ingot obtained in step 1) was homogenized at 1050°C for 12 hours in an electric heating furnace (5X-12-11) to obtain a homogenized alloy ingot. The surface oxides and defects were removed by mechanical milling. After being kept at 980°C for 1 hour, the homogenized alloy ingot was forged into an alloy plate of 80 mm × 200 mm × 10 mm, with a forging deformation of 60%. The surface oxides were removed by mechanical cutting (the turning thickness was about 2 mm), and then the alloy plate was solution treated at 900°C for 3 hours. After quenching in water at room temperature for 30 seconds, the quenched alloy plate is cold rolled to a thickness of 0.8 mm on a two-roll mill without intermediate annealing, and the total thickness is reduced by 90%, that is, the deformation is 90%. During the cold rolling process, in order to avoid strong temperature changes, the thinning amount per pass, that is, the deformation amount, is 5%. Subsequently, the cold-rolled strip is aged at an aging temperature of 400°C and an aging time range of 300 minutes, and then air-cooled to room temperature to obtain a Cu-19Ni-6Cr-7Mn alloy, which is the high-strength and corrosion-resistant copper alloy of Example 1.
[0035] Example 2
[0036] The preparation method of the high-strength corrosion-resistant copper alloy of this embodiment is basically the same as that of Example 1, except that: in step 1), according to the following copper alloy composition: Ni 21%, Cr 7%, Mn 7% and the balance copper, the raw materials are pure copper (99.99%), electrolytic manganese (99.99%) and Ni / Cr=3 (mass ratio) Ni-Cr intermediate alloy are smelted; the smelting temperature is controlled at 1280°C, and the pouring temperature is controlled at 1180°C; and a Cu-21Ni-7Cr-7Mn copper alloy ingot is obtained.
[0037] 3. Experimental Examples
[0038] This experimental example tests the mechanical properties and corrosion resistance of copper alloy.
[0039] Mechanical properties test: The tensile strength is tested according to the national standard GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method", and the elastic modulus is measured according to ASTM E111-04 (GB / T 22315-2008).
[0040] The specific test method for corrosion resistance is: an immersion experiment is carried out in accordance with the standard GB / T 39534-2020 "Determination of Uniform Corrosion Rate of Stainless Steel and Nickel-Based Alloys in Corrosive Liquids of Metals and Alloys", the corrosive medium is 3.5wt.% NaCl solution, the test temperature is room temperature 25°C, and the immersion time is 30 days.
[0041] A method for preparing a copper alloy without introducing Cr through an alloy is taken as comparative example 1. The specific preparation method is as follows: the preparation method of the copper alloy in comparative example 1 is basically the same as that in Example 1, except that: during smelting and casting in step 1), pure copper (99.99%), electrolytic manganese (99.99%), pure nickel, and pure chromium raw materials are directly smelted, and Ni-Cr intermediate alloy is not used.
[0042] The test results of mechanical properties and corrosion resistance of the embodiments and comparative examples are shown in Table 1. As can be seen from Table 1, compared with directly smelting the raw materials without using the Ni-Cr master alloy (Comparative Example 1), the tensile strength and elastic modulus of the copper alloys of Embodiments 1 and 2 are greatly improved, and the annual average corrosion rate is reduced by nearly 70%, indicating that by using the Ni-Cr master alloy for smelting, the uniform dispersion distribution of the Cr element in the matrix can be greatly improved, thereby greatly improving the mechanical properties and corrosion resistance of the alloy.
[0043] Table 1 Mechanical properties and corrosion resistance test results
[0044]
[0045] The XPS test was used to analyze the compound types of the corrosion product film of the copper alloy of Example 1 after the corrosion resistance test to evaluate its corrosion mechanism. The XPS peak fitting method was used to obtain the Cu 2p, Ni 2p, Cr 2p and Mn 2p spectra of the corrosion product film of the Cu-19Ni-6Cr-7Mn alloy after immersion in 3.5wt% NaCl solution for 30 days. Figure 1 (Binding strength-peak intensity curve diagram), and the fitting parameters are shown in Table 2. Figure 1 (a) is the Cu 2p spectrum of the corrosion product layer of Cu-19Ni-6Cr-7Mn alloy. Figure 1 As can be seen in (a), Cu2O and CuO appear at binding energies of 932.66eV and 934.93eV, respectively, with contents of 15% and 85%, respectively. The presence of Cu2O indicates that after immersion for 30 days, the copper oxide is mainly high-valent copper oxide, and the compound is relatively stable. It is worth mentioning that CuCl and Cu2(OH)3Cl, which usually appear in the corrosion layer, are not found in the XPS spectrum; Figure 1 (b) is the Ni 2p spectrum of the corrosion product layer of Cu-19Ni-6Cr-7Mn alloy. Figure 1 As can be seen in (b), the Ni 2p spectrum shows three peaks, NiO (856.14 eV), Sat. (858.6 eV) and Ni(OH)2 (862.43 eV). After immersion for 30 days, the alloy corrosion film mainly contains NiO (50%) and Ni(OH)2 (34%); Figure 1 (c) is the Cr 2p spectrum of the corrosion product layer of Cu-19Ni-6Cr-7Mn alloy. The Cr 2p spectrum was fitted and analyzed. The results showed that the binding energies centered at 576.2eV and 577.48eV were Cr2O3 and Cr(OH)3, respectively, both of which are Cr 3+ , the area proportion of Cr2O3 is 36%, and the formation of Cr2O3 can significantly enhance the protective ability of the corrosion product film; Figure 1 (d) is the Mn 2p spectrum of the corrosion product layer of Cu-19Ni-6Cr-7Mn alloy. Because the binding energy of MnO and Mn2O3 is similar, it is difficult to distinguish the two Mn 2p because it is defined as MnO / Mn2O3. Figure 1It can be seen from (d) that there are three peaks in Mn 2p, corresponding to Mn, MnO / Mn2O3 and MnO2, with binding energy centers of 638.54 eV, 641.7 eV and 645.03 eV, and area proportions of 23%, 42% and 35%, respectively. The results show that after 30 days of immersion corrosion, the corrosion products contain elements such as Cu, Ni, Cr, Mn and O. Mn mainly exists in the form of stable high-valent manganese. Mn2p has a variable diameter similar to that of Ni, so Ni can fill the cationic vacancies left by the precipitation of Mn2p, which can promote the enrichment of Ni in the corrosion film and improve the protective ability of the corrosion film. The corrosion product film mainly contains compounds such as Cu2O, CuO, NiO, Ni(OH)2, Cr2O3, Cr(OH)3, MnO / Mn2O3 and MnO2. The Cu2O, high content of Cr2O3 and MnO2 in the alloy corrosion product film hinder the transmission of corrosive media to the substrate to a certain extent, significantly reduce the corrosion rate of the copper alloy, and improve the corrosion performance of the alloy.
[0046] Table 2 Fitting parameters of XPS spectrum of Cu-19Ni-6Cr-7Mn alloy
[0047]
[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength corrosion-resistant copper alloy, characterized in that: The following steps are involved: According to the designed composition of the copper alloy, copper, manganese and Ni-Cr master alloy are melted and cast to obtain a copper alloy ingot, which is subjected to deformation heat treatment. The mass fraction of Cr in the copper alloy is 5-7%.
2. The method for preparing the high-strength corrosion-resistant copper alloy according to claim 1, characterized in that: The copper alloy consists of the following components in mass fraction: Ni 15-21%, Cr 5-7%, Mn 5-7% and the balance copper.
3. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 1, characterized in that: The smelting temperature is 1200-1300°C.
4. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 1, characterized in that: The pouring temperature during the casting is 1100-1200°C.
5. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 1, characterized in that: The deformation heat treatment includes homogenization treatment, forging, solution treatment, cold rolling and aging treatment performed in sequence.
6. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 5, characterized in that: The temperature of the homogenization treatment is 1000-1200° C., and the time of the homogenization treatment is 12-14 hours.
7. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 5, characterized in that: The deformation amount of the forging is 60% to 70%.
8. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 5, characterized in that: The temperature of the solution treatment is 800-900° C., and the time of the solution treatment is 3-5 hours.
9. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 5, characterized in that: The deformation amount of the cold rolling is 90-95%, and the cold rolling adopts multiple rolling passes, and the deformation amount of each pass is 5-6%.
10. The method for preparing a high-strength corrosion-resistant copper alloy according to claim 5, characterized in that: The temperature of the aging treatment is 400-700° C., and the time of the aging treatment is 300-500 min.
Citation Information
Patent Citations
A method for preparing a high-strength, high-corrosion-resistant Cu-Ni-Mn alloy
CN111004936B
A high-strength corrosion-resistant Cu-Ni-Sn alloy and preparation method thereof
CN115896537B
Cited By
Brittle corrosion-resistant metallic bond, metallic bond superhard grinding wheel and preparation method of metallic bond superhard grinding wheel
CN121946376A